TACTICAL SENSORY RADIO MEASURES - MULTISENSORY DETECTION AND LOCALIZATION OF AROUND OBJECTS. - Perepelitsyn, Sergii; Tereshchenko, Yaroslav; Shevchenko, Anatoly; Loza, Vitaly; Tereshchenko, Vasyl (Science-based technologies, 2024)
Currently, in the air defense system of units of the national security and defense sector of Ukraine, despite the constant updating (replenishment) of the park with modern models, there are still shortcomings in the system of detecting air targets of the surface layer with a small and ultra-small effective scattering surface. One of the most effective and cost-effective, from the point of view of financial and time resources, approaches is the creation of a modern tactical level information platform. Such a platform is based on the use of passive (seismic, acoustic, optical-electronic, magnetic, infrared, and other) sensors in military radio network structures compatible with the geographic information system (GIS) to identify targets of the surface layer that pose threats to military and infrastructure facilities of Ukraine. This article is dedicated to a thorough analysis of the routing management algorithm in sensor radio networks, with a focus on enhancing their stability and reliability. The authors concentrate on challenges associated with complex network operating conditions, such as instability of network interfaces, equipment failures, and various external and internal interferences that can negatively impact network performance. Special attention is given to the use of Gaussian Mixture Models (GMM) for modeling multimodal data, which allows for increased accuracy and efficiency in routing management. The results presented in the article demonstrate that the proposed algorithm has high accuracy, as confirmed by comparison with data obtained through simulation modeling. This indicates the practical applicability of the algorithm in real-world conditions. The research opens new perspectives for improving the stability and reliability of sensor radio networks, which is particularly relevant in the context of widespread use of wireless technologies. The proposed algorithm can be used to develop more reliable and efficient routing management systems, ensuring better adaptation to the changing conditions and challenges faced by modern wireless networks.